Effects of training system and cluster thinning on the composition of Merlot grapes - González-Neves, G.; Ferrer, M. (Agrociencia Uruguay, 2008)
The vineyard training and the cluster thinning were employing for the control of the equilibrium between the leaves and the fruits, thus produced grapes with adequate composition for the elaboration of wines with good quality. The aim of this work was to evaluate the effects of training system and cluster thinning on the composition of Merlot grapes. The assays were conducted in commercial vineyards of the south of Uruguay trained in lyre and trellis, in 2002, 2003 and 2004. Cluster thinning was done in veraison, at 50% of bunches relating to the control plants. At the harvest, the grape production was weighted per plant and grapes samples were taken. They were analyzed determining the soluble solids contents, total acidity, pH, berry weight and the proportions of skins, seeds and pulp. Polyphenolic potential was analysed according to Glories and Augustin (1993) and González-Neves (2005). Grape production was significantly higher in lyre, including the cluster thinning treatment. However, the lyre allow to obtain grapes with similar or superior contents in quality components (sugars, anthocyanins, skin tannins) that those obtained with trellis. The cluster thinning determined an improvement in the oenological quality of the grapes, although this effect was diverse according to the vineyards and the vintage. This practice determined total polyphenolic contents significantly higher in the majority of the situations, with increments in the contents in anthocyanins and tannins of the grapes.